a, 25-x2+(x+5)x(2x+1)
b,x2-2x-24=0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(\Leftrightarrow\left(x-5\right)\left(x+1\right)\left(x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=5\\x=-1\\x=1\end{matrix}\right.\)
d: \(\Leftrightarrow\left(x+3\right)\left(x^2-4x+5\right)=0\)
\(\Leftrightarrow x+3=0\)
hay x=-3
a) x = 1; x = - 1 3 b) x = 2.
c) x = 3; x = -2. d) x = -3; x = 0; x = 2.
`#040911`
`a)`
`(2x - 1)^2 - (2x + 5)(2x + 1) = 10`
`\Leftrightarrow 4x^2 - 4x + 1 - (4x^2 + 12x + 5) = 10`
`\Leftrightarrow 4x^2 - 4x + 1 - 4x^2 - 12x - 5 = 10`
`\Leftrightarrow (4x^2 - 4x^2) - (4x + 12x) + (1 - 5) = 10`
`\Leftrightarrow -16x - 4 = 10`
`\Leftrightarrow -16x = 10 + 4`
`\Leftrightarrow -16x = 14`
`\Leftrightarrow x = \dfrac{-7}{8}`
Vậy, `x= \dfrac{-7}{8}`
`b)`
`9^2(x - 1) + 25(1 - x) = 0`
`\Leftrightarrow 9^2(x - 1) - 25(x - 1) = 0`
`\Leftrightarrow (x - 1)(9^2 - 25) = 0`
`\Leftrightarrow`\(\left[{}\begin{matrix}x-1=0\\9^2-5^2=0\end{matrix}\right.\)
`\Leftrightarrow`\(\left[{}\begin{matrix}x=1\\\left(9-5\right)\left(9+5\right)=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=1\\4\cdot14=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=1\\56=0\left(\text{vô lý}\right)\end{matrix}\right.\\ \text{Vậy, x = 1}\)
`c)`
\(x^2+3x-4=0\)
`\Leftrightarrow x^2 + 4x - x - 4 = 0`
`\Leftrightarrow (x^2 - x) + (4x - 4) = 0`
`\Leftrightarrow x(x - 1) + 4(x - 1) = 0`
`\Leftrightarrow (x + 4)(x - 1) = 0`
\(\Leftrightarrow\left[{}\begin{matrix}x+4=0\\x-1=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=-4\\x=1\end{matrix}\right.\\ \text{ Vậy, }x\in\left(-4;1\right)\)
\(a,x^2-10x=-25\)
\(< =>x^2-10x+25=0\)
\(< =>\left(x-5\right)^2=0< =>x=5\)
b, \(4x^2-4x=-1\)
\(< =>4x^2-4x+1=0\)
\(< =>\left(2x-1\right)^2=0< =>x=\frac{1}{2}\)
a) Ta có: \(\left(x^2-5x\right)^2+10\left(x^2-5x\right)+24=0\)
\(\Leftrightarrow\left(x^2-5x\right)^2+4\left(x^2-5x\right)+6\left(x^2-5x\right)+24=0\)
\(\Leftrightarrow\left(x^2-5x\right)\left(x^2-5x+4\right)+6\left(x^2-5x+4\right)=0\)
\(\Leftrightarrow\left(x^2-5x+6\right)\left(x^2-5x+4\right)=0\)
\(\Leftrightarrow\left(x^2-2x-3x+6\right)\left(x^2-x-4x+4\right)=0\)
\(\Leftrightarrow\left[x\left(x-2\right)-3\left(x-2\right)\right]\left[x\left(x-1\right)-4\left(x-1\right)\right]=0\)
\(\Leftrightarrow\left(x-1\right)\left(x-2\right)\left(x-3\right)\left(x-4\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-1=0\\x-2=0\\x-3=0\\x-4=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=1\\x=2\\x=3\\x=4\end{matrix}\right.\)
Vậy: S={1;2;3;4}
b) Ta có: \(\left(2x+1\right)^2-2x-1=2\)
\(\Leftrightarrow\left(2x+1\right)^2-\left(2x+1\right)-2=0\)
\(\Leftrightarrow\left(2x+1\right)^2-2\left(2x+1\right)+\left(2x+1\right)-2=0\)
\(\Leftrightarrow\left(2x+1\right)\left(2x+1-2\right)+\left(2x+1-2\right)=0\)
\(\Leftrightarrow\left(2x+1+1\right)\left(2x-1\right)=0\)
\(\Leftrightarrow\left(2x+2\right)\left(2x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}2x+2=0\\2x-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}2x=-2\\2x=1\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-1\\x=\dfrac{1}{2}\end{matrix}\right.\)
Vậy: \(S=\left\{-1;\dfrac{1}{2}\right\}\)
c) Ta có: \(x\left(x-1\right)\left(x^2-x+1\right)-6=0\)
\(\Leftrightarrow x\left(x^3-x^2+x-x^2+x-1\right)-6=0\)
\(\Leftrightarrow x\left(x^3-2x^2+2x-1\right)-6=0\)
\(\Leftrightarrow x^4-2x^3+2x^2-x-6=0\)
\(\Leftrightarrow x^4-2x^3+2x^2-4x+3x-6=0\)
\(\Leftrightarrow x^3\left(x-2\right)+2x\left(x-2\right)+3\left(x-2\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(x^3+2x+3\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(x^3-x+3x+3\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left[x\left(x^2-1\right)+3\left(x+1\right)\right]=0\)
\(\Leftrightarrow\left(x-2\right)\left[x\left(x-1\right)\left(x+1\right)+3\left(x+1\right)\right]=0\)
\(\Leftrightarrow\left(x-2\right)\left(x+1\right)\left(x^2-x+3\right)=0\)
mà \(x^2-x+3>0\forall x\)
nên (x-2)(x+1)=0
\(\Leftrightarrow\left[{}\begin{matrix}x-2=0\\x+1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=2\\x=-1\end{matrix}\right.\)
Vậy: S={2;-1}
d) Ta có: \(\left(x^2+1\right)^2+3x\left(x^2+1\right)+2x^2=0\)
\(\Leftrightarrow\left(x^2+1\right)^2+2x\left(x^2+1\right)+x\left(x^2+1\right)+2x^2=0\)
\(\Leftrightarrow\left(x^2+1\right)\left(x^2+1+2x\right)+x\left(x^2+1+2x\right)=0\)
\(\Leftrightarrow\left(x+1\right)^2\cdot\left(x^2+x+1\right)=0\)
mà \(x^2+x+1>0\forall x\)
nên x+1=0
hay x=-1
Vậy: S={-1}
`#040911`
`a)`
\(\left(2x-1\right)^2-\left(2x+5\right)\left(2x+1\right)=10\)
\(\Leftrightarrow 4x^2 - 4x + 1 - (4x^2 + 12x + 5) = 10 \\ \Leftrightarrow 4x^2 - 4x + 1 - 4x^2 - 12x - 5 = 10 \\ \Leftrightarrow (4x^2 - 4x^2) - (4x + 12x) + (1 - 5) = 10 \\ \Leftrightarrow -16x - 4 = 10 \Leftrightarrow -16x = 10 + 4 \\ \Leftrightarrow -16x = 14 \\ \Leftrightarrow x = \dfrac{-7}{8}\)
Vậy, `x = -7/8`
`b)`
`9^2(x - 1) + 25(1 - x) = 0`
`<=> 9^2(x - 1) - 25(x - 1) = 0`
`<=> (x - 1)(9^2 - 5^2) = 0`
`<=>`\(\left[{}\begin{matrix}x-1=0\\9^2-5^2=0\end{matrix}\right.\)
`<=>`\(\left[{}\begin{matrix}x=1\\56=0\left(\text{vô lý}\right)\end{matrix}\right.\)
Vậy, `x = 1`
`c)`
`x^2+3x - 4 = 0`
`<=> x^2 + 4x - x - 4 = 0`
`<=> (x^2 - x) + (4x - 4) = 0`
`<=> x(x - 1) + 4(x - 1) = 0`
`<=> (x + 4)(x - 1) = 0`
\(\Leftrightarrow\left[{}\begin{matrix}x+4=0\\x-1=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=-4\\x=1\end{matrix}\right.\\ \text{Vậy, }x\in\left\{-4;1\right\}\)
a: =>4x^2-4x+1-(4x^2+2x+10x+5)=10
=>4x^2-4x+1-10-4x^2-12x-5=0
=>-16x-4=0
=>x=-1/4
b: =>(x-1)(9^2-25)=0
=>x-1=0
=>x=1
c: =>x^2+4x-x-4=0
=>(x+4)(x-1)=0
=>x=1 hoặc x=-4
a) \(25-x^2+\left(x+5\right)\left(2x+1\right)\)
\(=\left(5-x\right)\left(5+x\right)+\left(x+5\right)\left(2x+1\right)\)
\(=\left(x+5\right)\left(5-x+2x+1\right)\)
\(=\left(x+5\right)\left(x+4\right)\)
b) \(x^2-2x-24\)
\(=x^2-2x+1-25\)
\(=\left(x-1\right)^2-25\)
\(=\left(x-1-5\right)\left(x-1+5\right)\)
\(=\left(x-6\right)\left(x+4\right)\)